(Un)special Favors: Gratitude for Group-Based Benefits. Issue 1 (2nd January 2021) - Tsang, Jo-Ann
ABSTRACT: Because humans are social creatures, we often experience benefits on a group-level. Yet gratitude research has focused on single recipients largely to the exclusion of groups. Do people still experience gratitude, even if the recipient is broader than themselves? 2 experiments contrast the effects of group-based versus individual-based favors on gratitude. Undergraduate participants read scenarios where single benefactors provided recipients with either a group-based or individual benefits. When only group level was manipulated (Study 1, N = 122), participants showed more gratitude, indebtedness, and intention to reciprocate for individual compared to group-level benefits. When both group based benefits and benefactor motivations were manipulated (Study 2, N = 124), only motivations showed effects. Results suggest that people do experience gratitude for group-level favors, and group favors may influence gratitude-relevant attributions of motivation.